Past and Future Shifts in Marine Species Distributions Across Two South American Large Marine Ecosystems - Maria Bas; Sofía Diéguez Díaz; Jazel Ouled‐Cheikh; Marta Coll (Journal of Biogeography, 2026)
Aim To quantify temporal (Middle Holocene, historical and future) and spatial changes in habitat suitability for marine species in two South American Large Marine Ecosystems, and to evaluate the ecological consistency of long‐term Species Distribution Model projections using archaeological records as independent evidence of past species occurrences. Location Humboldt Current and Patagonian Shelf Large Marine Ecosystems (LMEs). Time Period Middle Holocene (~8200–4200 years BP), present day (1850–2014), and a projected future warming scenario (2015–2099; SSP5‐8.5). Major Taxa Studied Marine fish, penguins and pinnipeds. Methods SDMs were developed for nine marine species using present‐day occurrence records and contemporary environmental predictors. Models were projected to Middle Holocene climatic conditions and to a future high‐emissions scenario. Archaeological records of fish, penguins and pinnipeds from the Middle Holocene were compiled and used as proxies for past species occurrences to evaluate model projections through time. Results Bathymetry emerged as a key predictor of habitat suitability for most species. Projections revealed pronounced temporal and spatial shifts in suitable habitat. Most fish species showed higher suitability at higher latitudes during the Middle Holocene, followed by contractions in the historical period and future projection. Penguin species exhibited heterogeneous responses, with several showing strong declines in future suitable habitat. Pinniped species displayed mixed patterns of contraction and expansion depending on region and time period. Comparison with archaeological records indicated that seven of the nine SDMs correctly identified suitable habitats consistent with Middle Holocene occurrences. Main Conclusions Zooarchaeological data provide an independent line of evidence to assess the temporal robustness of marine SDMs. Incorporating past climatic periods improves confidence in long‐term biogeographical projections and enhances understanding of species' distributional dynamics under climate change.

Understanding forest transitions and lock-ins in Latin American agro-forest frontiers: aligning theory to practice for accelerating restoration - Madelon Lohbeck; Thomas W. Kuyper; Frans Bongers; Rocío Aguilar-Fernández; Patricia Balvanera; Jelle Behagel; Carolina Berget; Felix Bianchi; Irene Maria Cardoso; Lucas de Carvalho Gomes; Juana Cruz-Morales; Mathieu Decuyper; et al. (Global Environmental Change, 2026)

A new Western Mediterranean Sea EBSAs proposal based on quantitative information of key criteria - Maria Bas; Miquel Ortega; Francisco Ramírez; Jeroen Steenbeek; Marta Coll (Marine Policy, 2026)

Modelling Palaeodistributions in Marine Environments: A Review - Sarah Mathilde Salomé Beauvais; Emna Ben Lamine; Konstantina Agiadi; Maria Bas; Grégory Beaugrand; Tatiana Theodoropoulou; Virginie Raybaud (Journal of Biogeography, 2026)
Aim This scoping review (ScR) synthesises the current literature on the application of Species Distribution Models (SDM) to past marine environments. We assess how these models have been used to reconstruct past environmental suitability, track biogeographical shifts and investigate long‐term ecological dynamics, while identifying key knowledge gaps and methodological uncertainties related to data availability, biases and modelling approaches. Location Worldwide. Taxon Marine invertebrates, fishes, seabirds, cetaceans and foraminifera. Methods This review examines the application of SDM to reconstruct past marine species distributions through a systematic synthesis of the literature following PRISMA guidelines. A total of 37 studies were included, spanning diverse taxa, geographic regions and time periods from the Late Ordovician to the Holocene. Results Marine palaeo‐SDM reveal recurrent biogeographic responses to climatic change, including glacial range contractions, interglacial expansions, bathymetric redistributions and the persistence of oceanographically structured refugia. Reconstructed distributions highlight the role of sea‐level fluctuations, circulation patterns and productivity gradients in shaping connectivity, fragmentation and population structure. Integrating palaeo‐SDM with phylogeographic and fossil evidence further demonstrates how past climatic events influenced contemporary genetic diversity and dispersal pathways across marine ecosystems. Main Conclusions Marine palaeo‐SDM indicate strong climatic control on species distributions across space and time, but uncertainties linked to fossil data limitations, palaeoclimate variability and SDM algorithms remain substantial, particularly under non‐analogue climatic conditions. Future studies should expand spatial and temporal coverage, integrate ecological and multi‐proxy data and explicitly incorporate uncertainty through probabilistic and ensemble approaches to improve reconstructions of past marine biodiversity dynamics and predictions under ongoing climate change.

Neuropathogenesis of Usutu virus-associated disease in Eurasian blackbirds (Turdus merula) involves apoptosis through the extrinsic pathway - Giuseppe Giglia; Gianfilippo Agliani; Bas B. Oude Munnink; Reina S. Sikkema; Maria Teresa Mandara; Christine Fast; Marleen Gosens; Eefje J. A. Schrauwen; Erwin de Bruin; Andrea Gröne; Judith M. A. van den Brand (Journal of NeuroVirology, 2026)
Usutu virus (USUV) is a zoonotic arbovirus causing systemic and neuroinvasive diseases in birds and flu-like or sporadic neuroinvasive disease in humans. USUV-associated encephalitis is morphologically well-characterized in birds, while the mechanisms of cell-damage in spontaneously infected birds remain poorly understood. For the closely related West Nile virus, apoptosis significantly contributes to the pathogenesis of othoflavivirus-induced neuropathology. This study investigates the involvement of apoptosis in USUV-associated encephalitis in Eurasian blackbirds ( Turdus merula ). To determine the apoptosis involvement, immunohistochemistry for cleaved-caspase-3 (CC3), TUNEL-assay, and RT-qPCR to compare mRNA expression levels of caspase 8 (extrinsic pathway) and caspase 9 (intrinsic pathway) were performed on brains of USUV-infected ( n = 26) and USUV-uninfected ( n = 16) blackbirds, as well as Africa 3 and Europe 3 USUV-lineages. The results showed a higher CC3 expression in USUV-infected (m = 231,96 ± 117,033) compared to uninfected blackbirds (m = 22,00 ± 13,31) ( p < 0.001). Similarly, higher TUNEL-positive cell counts were detected in USUV-infected (m = 197,00 ± 83,56) compared to uninfected blackbirds (m = 19,00 ± 16,08) ( p < 0.01). No significant differences were detected comparing Africa 3 and Europe 3 lineages. Additionally, both caspases were upregulated in USUV-infected blackbirds. Caspase 8 was in average 4,37 ± 0,89 (CI α = 0,05) times higher in USUV-infected blackbirds ( p < 0.0001), while caspase 9 expression was in average 1,82 ± 0,89 (CI α = 0,05) times higher in USUV-infected blackbirds ( p < 0.01). Although both apoptotic pathways are involved, the extrinsic pathway is notably more active in USUV-infected blackbirds, highlighting its role in USUV-associated brain damage.

Agronomic constraints limit the climate change mitigation potential of winter cover crops in Europe - Marti Vidal Morant; Sarah-Maria Scheid; Bas du Mortier; Charlotte van Haren; Allard de Wit; Renske Hijbeek (European Journal of Agronomy, 2026)

Small-scale sea urchin (Tripneustes gratilla) aquaculture: evaluating locally sourced diets for gonad development and quality - Shamira Payet; Maria Rose; Danilla Adonis; Zachary Morin; Aubrey Lesperance; Devis Monthy; Lawrence Grant; Bas De Vos (Western Indian Ocean Journal of Marine Science, 2026)
Sea urchin gonads (called uni) are highly valued in seafood markets, creating demand for sustainable production. In Seychelles, small-scale farming of Tripneustes gratilla is promising, but costly pelleted feeds for gonad enhancement limit feasibility. This study evaluated alternative fresh feeds, Sargassum spp., carrots (Daucus carota), moringa (Moringa oleifera), and a mixed diet, over 10 weeks using 200 T. gratilla (average wet weight: 492.6 ± 79.37 g). Gonad quality was assessed at weeks 6, 8, and 10, alongside disease and mortality monitoring. The overall mean gonadosomatic index (GSI) was 3.34 %, peaking at 10.38 % in week 8. Significant differences were found among feed types and durations (p 0.113), texture (p > 0.071), or firmness (p > 0.064). Mortality and disease rates were also unaffected (p > 0.415 and p > 0.963). Although no tested diet improved gonad quality, the potential for artisanal T. gratilla farming may remain, but likely depends on improved enhancement diets and/or locally feasible formulated feeds, which require further evaluation.

Community response in highly dynamic ecosystems: the case of zooplankton from Mediterranean coastal ponds - Maria Anton-Pardo; Maria Bas-Silvestre; Dani Boix; Jordi Compte; Stéphanie Gascón; Anna Menció; Jordi Sala; Xavier D. Quintana (Hydrobiologia, 2025)
The inherent nature of coastal ponds and their small size make them highly dynamic ecosystems, with great variations in their environmental conditions, such as changes in conductivity (due to sea storms or freshwater inputs), water level, or dissolved oxygen (DO) concentration. Because of these frequent fluctuations, aquatic communities are generally adapted to them, which often hinders the detection of the effects of disturbances on aquatic assemblages (“the Estuarine Quality Paradox”). Using high-frequency sondes, daily fluctuations in conductivity and water level, and hypoxia episodes were detected over more than one year in four coastal ponds showing differences in their degree of water circulation. The effects of these fluctuations on monthly zooplankton community attributes (abundance, biomass, richness, diversity, and size diversity and evenness) were analysed. The results showed that the environmental fluctuations had a limited influence on zooplankton community attributes, highlighting the adaptation of species to environmental variations in coastal habitats. These fluctuations did not produce major changes in assemblage composition nor community homogenization. In addition, the degree of water circulation rate influenced the occurrence and number of fluctuations, with a seasonal and predictable pattern of fluctuations in confined ponds, while in the ponds with higher circulation, environmental variations were more unpredictable.

Low mercury content in Seychelles seaweed: implications for aquaculture expansion - Bas De Vos; Shamira Payet; Maria Rose; Clémentine Violette; Rona Arrisol; Margaret Ally-Nourrice; Aubrey Lesperance; Devis Monthy (Western Indian Ocean Journal of Marine Science, 2025)
Stable tropical conditions and a near-pristine marine environment in the Seychelles suggest a high potential for seaweed aquaculture to supply growing global markets for sustainable marine products. The aims of this study were to assess the mercury content in five seaweed species that are candidates for aquaculture in Seychelles: Gracilaria cortica, Gracilaria salicornia, Caulerpa racemosa, Sargassum spp., and Asparagopsis taxiformis. Mercury contamination is a significant con- cern in seaweed aquaculture because it may bioaccumulate, potentially affecting human health when derived products are used. Samples were collected from different sites in Seychelles, categorized as polluted or unpolluted, to evaluate the influence of environmental factors on mercury accumulation. The results showed that mercury contents were low across all tested seaweed species and sites, with the highest observed content of 0.0038 mg/kg (wet weight), well below international safety limits. Significant differences were found between species; however, site pollution level did not significantly influence mercury content. Low mercury content, in addition to a favourable physical environment, confirm that the region is suitable for seaweed aquaculture. It is recommended that other heavy metal concentrations are also assessed, to pro- vide a comprehensive safety evaluation of seaweed aquaculture in Seychelles.

Investigating the feasibility and conditions for outdoor microalgae cultivation in Seychelles - Maria Rose; Shamira Payet; Clementine Violette; Danilla Adonis; Zachary Morin; Aubrey Lesperance; Bas De Vos (Western Indian Ocean Journal of Marine Science, 2025)
Microalgae play a critical role in aquaculture hatcheries as a primary feed source, supplying lipids, proteins, and vitamins to nearly all aquaculture species. Traditionally cultivated indoors under controlled conditions, microalgae production is resource intensive. This study examines the potential for outdoor microalgae farming in equatorial regions like Seychelles, utilizing abundant sunlight and stable high temperatures for a more cost-effective, sustainable approach. By minimizing the reliance on sophisticated facilities, this approach can increase accessibility for a broader range of aquaculture practitioners. This research investigates the feasibility of outdoor cultivation and seeks to identify optimal light and temperature conditions for growing Tetraselmis spp. and Chaetoceros muelleri, chosen for their hardiness and importance to various aquaculture species. A factorial experimental design was employed with four treatments: shaded, unshaded, cooling system, and non-cooling system, alongside an indoor control. The results indicated that C. muelleri reached the highest cell density of 887,000 cells/ml in the unshaded-cooled treatment (24.4°C to 34.4°C). Whereas Tetraselmis spp. achieved peak cell density of 159,000 cells/ml indoors at 28.9°C, though unshaded-cooled outdoor treatments may also support growth, pending further investigation. The research seeks to determine the feasibility and optimal growing conditions for outdoor microalgae production in Seychelles and similar climates.

Straight from the horse's mouth: Changes in salivary oxytocin, cortisol and behaviour in horses interacting with unfamiliar humans - Chantal Maria Kapteijn; Claudia Maureen Vinke; Hein van Lith; Nienke Endenburg; T. Bas Rodenburg; Jean-Loup Rault (Applied Animal Behaviour Science, 2025)

Operationalising Ecologically or Biologically Significant Marine Areas criteria for ecosystem-based conservation and management: The Bay of Biscay case - Olga Lukyanova; Sarai Pouso; Isabel García-Barón; Angel Borja; Maria Bas; Roland Cormier; Stelios Katsanevakis; Stefan Neuenfeldt; Vanessa Stelzenmüller; Ibon Galparsoro (Biological Conservation, 2025)

Changes in community composition and functional diversity of European bats under climate change - Penelope C. Fialas; Luca Santini; Danilo Russo; Francisco Amorim; Hugo Rebelo; Roberto Novella‐Fernandez; Francisco Marques; Adi Domer; Adriana Vella; Adriano Martinoli; Aleksandra Figurek; Asaf Tsoar; et al. (Conservation Biology, 2025)
Climate change is predicted to drive geographical range shifts that will result in changes in species diversity and functional composition and have potential repercussions for ecosystem functioning. However, the effect of these changes on species composition and functional diversity (FD) remains unclear, especially for mammals, specifically bats. We used species distribution models and a comprehensive ecological and morphometrical trait database to estimate how projected future climate and land‐use changes could influence the distribution, composition, and FD of the European bat community. Future bat assemblages were predicted to undergo substantial shifts in geographic range and trait structure. Range suitability decreased substantially in southern Europe and increased in northern latitudes. Our findings highlight the potential for climate change to drive shifts in bat FD, which has implications for ecosystem function and resilience at a continental scale. It is important to incorporate FD in conservation strategies. These efforts should target species with key functional traits predicted to be lost and areas expected to experience losses in FD. Conservation strategies should include habitat and roost protection, enhancing landscape connectivity, and international monitoring to preserve bat populations and their ecosystem services.

Fishing activities within Spanish marine protected areas in the Mediterranean Sea - María D. Castro-Cadenas; Martín Barreiros; Maria Bas; Miquel Ortega; Joachim Claudet; Marta Coll; Valerio Sbragaglia (Marine Policy, 2025)

Usutu virus-disease susceptibility in threatened red-breasted geese (Branta ruficollis) in Italy and the Netherlands - Giuseppe Giglia; Emmanuelle Münger; Giulia Mencattelli; Gianfilippo Agliani; Alinda J. Berends; Fabrizia Valleriani; Giorgio Filipponi; Stefano Gavaudan; Annapia Di Gennaro; Christine Fast; Reina S. Sikkema; Marja Kik; et al. (Journal of Comparative Pathology, 2025)

Assessing the potential for red seaweed Asparagopsis taxiformis aquaculture in Seychelles - Bas De Vos; Shamira Payet; Maria Rose; Danila Adonis; Zachary Morin; Devis Monthy; Lawerence Grant; Mookho Lerata; Denzil Beukes; Aubrey Lesperance (Western Indian Ocean Journal of Marine Science, 2025)
Asparagopsis taxiformis macroalgae can potentially reduce methane emissions when fed to ruminants, thus reducing the emission of greenhouse gasses into the atmosphere. Literature indicates water temperatures above 24 °C limit A. taxiformes growth rates during culture, however, it grows wild in Seychelles where water temperatures range from 25 to 31.5 °C. The feasibility of cultivating the local strain of A. taxiformis in Seychelles was investigated, focusing on growth rates at higher temperatures and bromoform content, the compound responsible for methane reduction. Two tetrasporophyte growth trials were conducted in photobioreactors at 24 °C, 26 °C, 29 °C and 32 °C. In the first trial, unacclimated specimens showed poor growth, with no significant differences between temperatures. In the second trial, daily growth rates of acclimated specimens were 3.98 % across all temperatures, including 32 °C, where temperature did not significantly affect growth. Bromoform concentrations were lower than expected, likely due to storage conditions prior to sample processing. The local strain of A. taxiformis in Seychelles may therefore be adapted to higher temperatures, with potential for aquaculture. Further research to optimize cultivation techniques and ensure adequate bromoform content is required.

Potential Spatial Mismatches Between Marine Predators and Their Prey in the Southern Hemisphere in Response to Climate Change - Maria Bas; Jazel Ouled‐Cheikh; Alba Fuster‐Alonso; Laura Julià; David March; Francisco Ramírez; Luis Cardona; Marta Coll (Global Change Biology, 2025)
Global change is rapidly reshaping species' habitat suitability ranges, hence leading to significant shifts in the distribution of marine life. Contrasting distributional responses among species can alter the spatial overlap between predators and prey, potentially disrupting trophic interactions and affecting food web dynamics. Here, we evaluate long‐term changes in the spatial overlap of habitat suitability ranges for trophically related species, including crustaceans, fish, penguins, and pinnipeds across 12 Large Marine Ecosystems from the Southern Hemisphere, merged into three primary regions: South America, Southern Africa, Australia and New Zealand. To this aim, we first use Boosted Regression Trees (BRTs) to hindcast and project species‐specific changes in suitable habitat from 1850 to 2100 under two future climate scenarios: SSP1‐2.6 (low climate forcing) and SSP5‐8.5 (high climate forcing). We then analyze changes in species habitat suitability and potential predator–prey spatial overlaps. Findings reveal that marine species generally exhibit changes in their suitable habitats, with pronounced shifts towards higher latitudes under the SSP5‐8.5 scenario. However, contrasting trends emerge among predators across functional groups and regions of South America, Southern Africa, Australia and New Zealand. These variations highlight the need for species and regional‐specific management responses. We also project contrasting spatial mismatches between predators and prey: predators experiencing declines in suitable habitat tend to exhibit greater overlap with their prey in future scenarios, whereas those with expanding suitable habitat show reduced spatial overlap with their prey. This study provides valuable insights that can inform spatial management strategies in response to climate change and illustrate how climate change may weaken species' ability to adapt to climate‐driven environmental changes due to trophic disruptions.

Uncovering the relationship between light intensity and Tripneustes gratilla (collector sea urchin): implications for aquaculture - Shamira Payet; Bas De Vos; Maria Rose; Danilla Adonis; Aubrey Lesperance; Thomas Hecht (Western Indian Ocean Journal of Marine Science, 2024)
The sea urchin species Tripneustes gratilla has high aquaculture potential. It is known for using debris to cover itself, likely to avoid light, which suggests that high light levels may impact its production. This study aimed to validate these concerns through four experiments. The first experiment assessed if T. gratilla preferred opaque or transparent covering materials, finding no evidence that shading ability of the material influenced their choice (F(2, 33) = 0.27, p = 0.765). The second experiment investigated the impact of shade on the number of covering materials collected, showing that higher solar radiation correlated with increased material collection per urchin (H(3) = 7.844, p = 0.049). The third experiment evaluated righting response time as a fitness trial, finding that high light intensity reduced fitness to urchins acclimated to low light (H(2) = 5.615, p = 0.020). The fourth long-term experiment demonstrated that T. gratilla can acclimatize to higher light intensities, with no significant differences in fitness, mortality, disease susceptibility, growth, and gonadosomatic index (p > 0.128). While this suggests that shading may not be a strict requirement for T. gratilla aquaculture, it is recommended for consideration. These findings underscore the importance of acclimatization when altering light conditions for T. gratilla.

The contribution of fish to the diet of loggerhead sea turtles in the western Mediterranean revisited - Luis Cardona; F. Javier Aznar; Maria Bas; Jesús Tomás (Marine Biology, 2024)
Early juvenile loggerhead turtles ( Caretta caretta ) rely on gelatinous zooplankton, whereas individuals larger than 40 cm curved carapace length are adapted to crush hard-shelled invertebrates. Nevertheless, fish were reported to be the staple food of loggerhead turtles in the western Mediterranean 30 years ago. Here, the temporal consistency of such a fish-based diet of loggerhead turtles is assessed through gut content analysis and stable isotope analysis of samples from the Mediterranean coast of Spain spanning three decades. The gut contents of 134 juvenile loggerhead turtles (curved carapace length range: 27–71 cm) from three different periods (1991, 1999–2008 and 2010–2017) were analyzed, as well as a subsample of the same turtles ( n = 10 in each period) for both bulk and compound-specific stable isotope ratios (CSIA-AA). Gut content analysis revealed a decline in the frequency of occurrence and numerical abundance of fish and an increasing contribution of gastropods and bivalves throughout time, although pelagic tunicates were always the most frequently observed prey. The δ 15 N bulk of turtle bone also dropped throughout the study period, but the values of the stable isotope ratio of N in phenylalanine (δ 15 N Phe ) indicated that 52.5% of that variability was due to a baseline shift over time. Accordingly, the trophic position estimated from CSIA-AA did not follow the decreasing pattern of δ 15 N bulk , but fluctuated throughout time. The overall evidence indicates that fish consumption by loggerhead turtles in the study region declined through time, but the trophic position of loggerhead turtles did not change simultaneously. This is probably because low trophic prey such pelagic tunicates and filter-feeding bivalves and suspension-feeding gastropods were the bulk of the diet during the whole study period and fish played a minor role, even when their frequency of occurrence peaked. Past levels of high fish consumption might be due to high levels of fishery discards, currently declining because of the recent reduction of the fishing fleet.

Fish and tips: Historical and projected changes in commercial fish species' habitat suitability in the Southern Hemisphere - Maria Bas; Jazel Ouled-Cheikh; Laura Julià; Alba Fuster-Alonso; David March; Francisco Ramírez; Luis Cardona; Marta Coll (Science of The Total Environment, 2024)

Towards integration of LOTOS-EUROS high resolution simulations and heterogenous low-cost sensor observations - Ioanna Skoulidou; Arjo Segers; Bas Henzing; Jun Zhang; Ruben Goudriaan; Maria-Elissavet Koukouli; Dimitrios Balis (Atmospheric Environment, 2024)

Phytoplankton composition in Mediterranean confined coastal lagoons: testing the use of ecosystem metabolism for the quantification of community-related variables - Maria Bas-Silvestre; Maria Antón-Pardo; Dani Boix; Stéphanie Gascón; Jordi Compte; Jordi Bou; Biel Obrador; Xavier D. Quintana (Aquatic Sciences, 2024)
Estimations of ecosystem metabolism have rarely been used to quantify productivity in structural reductionist approaches for the description of phytoplankton composition. However, estimations of ecosystem metabolism could contribute to a better understanding of the relationship between phytoplankton composition and ecosystem functioning. To examine this, we investigated the community structure of phytoplankton in a set of Mediterranean coastal lagoons (natural and artificial) during a hydrological cycle to identify the most important environmental variables determining phytoplankton species composition. The focus of the study was on the quantification of productivity-related variables using estimations of ecosystem metabolism, such as different proxies for the estimation of the production-to-biomass ratio and of the relative importance of K- and r -strategies, which are commonly used conceptually but not quantified. Our results demonstrated differences in phytoplankton composition between seasons, due to the dominant hydrological pattern of flooding confinement in the salt marsh, and between lagoons that were caused by different levels of nutrient availability. Moreover, there was a notable decrease in the production/biomass ratio and a prevalence of K -strategists with seasonal succession, as predicted by Margalef’s mandala. Thus, the results showed that estimations of ecosystem metabolism are useful for the higher frequency quantification of important ecological variables, and contribute to a better understanding of planktonic assemblages, and physical and chemical changes, in these fluctuating ecosystems.

The performance of global forest governance: Three contrasting perspectives - Bas Arts; Maria Brockhaus; Lukas Giessen; Constance L. McDermott (Forest Policy and Economics, 2024)

Reconstructed Human Skin with Hypodermis Shows Essential Role of Adipose Tissue in Skin Metabolism - Jonas Jäger; Irit Vahav; Maria Thon; Taco Waaijman; Bas Spanhaak; Michael de Kok; Ranjit K. Bhogal; Susan Gibbs; Jasper J. Koning (Tissue Engineering and Regenerative Medicine, 2024)
Background: Dysregulation of skin metabolism is associated with a plethora of diseases such as psoriasis and dermatitis. Until now, reconstructed human skin (RhS) models lack the metabolic potential of native human skin, thereby limiting their relevance to study human healthy and diseased skin. We aimed to determine whether incorporation of an adipocyte-containing hypodermis into RhS improves its metabolic potential and to identify major metabolic pathways up-regulated in adipose-RhS. Methods: Primary human keratinocytes, fibroblasts and differentiated adipose-derived stromal cells were co-cultured in a collagen/fibrin scaffold to create an adipose-RhS. The model was extensively characterized structurally in two- and three-dimensions, by cytokine secretion and RNA-sequencing for metabolic enzyme expression. Results: Adipose-RhS showed increased secretion of adipokines. Both RhS and adipose-RhS expressed 29 of 35 metabolic genes expressed in ex vivo native human skin. Addition of the adipose layer resulted in up-regulation of 286 genes in the dermal-adipose fraction of which 7 were involved in phase I (CYP19A1, CYP4F22, CYP3A5, ALDH3B2, EPHX3) and phase II (SULT2B1, GPX3) metabolism. Vitamin A, D and carotenoid metabolic pathways were enriched. Additionally, pro-inflammatory (IL-1β, IL-18, IL-23, IL-33, IFN-α2, TNF-α) and anti-inflammatory cytokine (IL-10, IL-12p70) secretion was reduced in adipose-RhS. Conclusions: Adipose-RhS mimics healthy native human skin more closely than traditional RhS since it has a less inflamed phenotype and a higher metabolic activity, indicating the contribution of adipocytes to tissue homeostasis. Therefore it is better suited to study onset of skin diseases and the effect of xenobiotics.

A critical reappraisal of paleomagnetic evidence for Philippine Sea Plate rotation - Suzanna H.A. van de Lagemaat; Daniel Pastor-Galán; Bas B.G. Zanderink; Maria J.Z. Villareal; John W. Jenson; Mark J. Dekkers; Douwe J.J. van Hinsbergen (Tectonophysics, 2023)

Shifts in the smart research agenda? 100 priority questions to accelerate sustainable energy futures - Rosie Robison; Tomas Moe Skjølsvold; Tom Hargreaves; Sara Renström; Maarten Wolsink; Emily Judson; Viera Pechancová; Melike Demirbağ-Kaplan; Hug March; Johanna Lehne; Chris Foulds; Zareen Bharucha; et al. (Journal of Cleaner Production, 2023)

Identifying critical transitions in seasonal shifts of zooplankton composition in a confined coastal salt marsh - Xavier D. Quintana; Maria Antón-Pardo; Maria Bas-Silvestre; Dani Boix; Xavier Casamitjana; Jordi Compte; David Cunilllera-Montcusí; Stéphanie Gascón; Anna Menció; Biel Obrador; Irene Tornero; Jordi Sala (Aquatic Sciences, 2021)
Zooplankton assemblages in the confined coastal lagoons of La Pletera salt marshes (Baix Ter wetlands, Girona, Spain) are dominated by two species: one calanoid copepod ( Eurytemora velox ) and the other rotifer ( Brachionus gr. plicatilis ). They alternate as the dominant species (more than 80% of total zooplankton biomass), with the former being dominant in winter and the latter in summer. Shifts between these taxa are sudden, and intermediate situations usually do not last more than 1 month. Although seasonal shifts between zooplankton dominant species appear to be related with temperature, other factors such as trophic state or oxygen concentration may also play an important role. Shifts between species dominances may be driven by thresholds in these environmental variables. However, according to the alternative stable states theory, under conditions of stable dominance a certain resistance to change may exist, causing that gradual changes might have little effect until a tipping point is reached, at which the reverse change becomes much more difficult. We investigated which are the possible factors causing seasonal zooplankton shifts. We used high-frequency temperature and oxygen data provided by sensors installed in situ to analyse if shifts in zooplankton composition are determined by a threshold in these variables or, on the other hand, some gradual change between stable states occur. Moreover, following the postulates of the alternative stable states theory, we looked at possible hysteresis to analyse if these seasonal zooplankton shifts behave as critical transitions between two different equilibriums. We also examined if top-down or bottom-up trophic interactions affect these zooplankton shifts. Our results show that shifts between dominant zooplankton species in La Pletera salt marshes are asymmetric. The shift to a Eurytemora situation is mainly driven by a decrease in temperature, with a threshold close to 19 °C of daily average temperature, while the shift to Brachionus does not. Usually, the decrease in water temperature is accompanied by a decrease in oxygen oscillation with values always close to 100% oxygen saturation. Moreover, oxygen and temperature values before the shift to calanoids are different from those before the reverse shift to Brachionus , suggesting hysteresis and some resistance to change when a critical transition is approaching. Top-down and bottom-up forces appear to have no significant effect on shifts, since zooplankton biomass was not negatively correlated with fish biomass and was not positively related with chlorophyll, in overall data or within shifts.

Applicability of the Goda–Takahashi Wave Load Formula for Vertical Slender Hydraulic Structures - Nadieh Elisabeth Meinen; Raphaël Daniël Johannes Maria Steenbergen; Bas Hofland; Sebastiaan Nicolaas Jonkman (Journal of Marine Science and Engineering, 2020)
Vertical slender hydraulic structures such as sluices, navigation locks, or storm-surge barriers are often dynamically loaded by waves. For a safe and economic design, an accurate description of the wave loads is needed. A widely used formula for this purpose is the Goda–Takahashi wave load formula (GT). It was derived for the assessment of gravity-based caisson breakwaters. Due to its many advantages, the formula is also often employed for the assessment of vertical slender hydraulic structures, although its applicability to those type of structures was never fully demonstrated. This study provides insights in the applicability of GT for vertical slender hydraulic structures. This is done based on a literature review on the historical backgrounds of GT, and an investigation of several case-studies. In the case-studies, the equivalent-static wave loads for caisson breakwaters in scope of GT are compared with those for vertical slender hydraulic structures. The results show that GT can safely be applied for vertical slender hydraulic structures loaded by pulsating wave loads, but that systematic over- or under-estimations are expected for breaking or impact wave loads. For individual cases, differences up to 200% were obtained. These large over- or under-estimations underline the need for an improvement of the current design tools for vertical slender hydraulic structures loaded by breaking or impact wave loads.

Phylogenetic characterization of marine microbial biofilms associated with mammal bones in temperate and polar areas - Sergi Taboada; Maria Bas; Conxita Avila; Ana Riesgo (Marine Biodiversity, 2020)

Predicting habitat use by the Argentine hake Merluccius hubbsi in a warmer world: inferences from the Middle Holocene - Maria Bas; Mónica Salemme; Eleanor Joan Green; Fernando Santiago; Camilla Speller; Myrian Álvarez; Ivan Briz i Godino; Luis Cardona (Oecologia, 2020)

Intraskeletal variability in stable isotope ratios of C and N among pinnipeds and cetaceans - Maria Bas; Néstor A. García; Enrique A. Crespo; Luis Cardona (Marine Mammal Science, 2020)

Inhibition of Semaphorin3A Promotes Ocular Dominance Plasticity in the Adult Rat Visual Cortex - Elena Maria Boggio; Erich M. Ehlert; Leonardo Lupori; Elizabeth B. Moloney; Fred De Winter; Craig W. Vander Kooi; Laura Baroncelli; Vasilis Mecollari; Bas Blits; James W. Fawcett; Joost Verhaagen; Tommaso Pizzorusso (Molecular Neurobiology, 2019)

Back to the future? Late Holocene marine food web structure in a warm climatic phase as a predictor of trophodynamics in a warmer South‐Western Atlantic Ocean - Maria Bas; Ivan Briz i Godino; Myrian Álvarez; Damián G. Vales; Enrique A. Crespo; Luis Cardona (Global Change Biology, 2019)
Stable carbon and nitrogen isotope ratios in the skeletal elements of both ancient and modern marine species from the Beagle Channel were used to compare the structure of Late Holocene and modern food webs, and predict potential changes as a result of a Sea Surface Temperature (SST) increase in the region. Complementary, ancient and modern shells of limpets and mussels were isotopically analysed to explore changes in the isotopic baseline and compare marine food webs through time after an appropriate correction for baseline shifts. Results confirmed a declining pattern of marine primary productivity during the Late Holocene in the Beagle Channel. In general, the isotopic niches overlapped largely in the ancient food web in comparison to the current marine one, with the exception of that of cormorants ( Phalacrocorax sp.). Our data suggest that all the species that have undergone intense human exploitation ( Arctocephalus australis , Otaria flavescens and Merluccius sp.) significantly increased their trophic levels. The most important finding of this work was the very high isotopic overlap between snoek ( Thyrsites atun ) and hake ( Merluccius sp.) during the Late Holocene. Increasing SST as a result of global warming could favour the recolonization of the southern South‐Western Atlantic Ocean by snoek from the South‐Eastern Pacific Ocean, with a potential impact on the landings of the economically important Argentine and Austral hake. These findings highlight the relevance of using zooarchaeological remains for providing predictions about marine food webs changes in the near future.

Cryptic species and colonization processes in Ophryotrocha (Annelida, Dorvilleidae) inhabiting vertebrate remains in the shallow‐water Mediterranean - Sergi Taboada; Carlos Leiva; Maria Bas; Nancy Schult; Damhnait McHugh (Zoologica Scripta, 2017)
Over the past several years, there has been growing interest in how bones of decaying mammals are colonized in the marine seabed. One of the most common opportunistic taxa occurring worldwide on bones is dorvilleid polychaetes of the genus Ophryotrocha . In a recent study in the Mediterranean, Ophryotrocha puerilis and Ophryotrocha alborana were two of the most abundant species occurring in experimentally deployed bones. These species have direct development and this makes them a suitable model to study the mechanisms and processes allowing organisms lacking a dispersive larval phase to colonize new substrates. Here, we address the colonization processes at the molecular level for populations of O. puerilis and O. alborana on experimentally deployed mammal bones in the shallow‐water Mediterranean collected over a year at 3‐month intervals. High genetic distances between some of the O. puerilis organisms collected indicated the occurrence of at least two cryptic sibling species ( O. puerilis ‘Shallow’ and O. puerilis ‘Deep’) apart from O. puerilis sensu stricto . This was corroborated with phylogenetic analyses using an alignment of three concatenated genes ( COI , 16S , H3 ) and with species delimitation analyses using COI . The haplotype network inferred from COI sequences for O. puerilis ‘Shallow’ showed a few common haplotypes shared between the two trimesters analysed and several other less represented haplotypes only present in one trimester. Thus, colonization of these experimental bones may have been achieved by a few organisms that arrived to the bones and were able to reseed, and by several individuals arriving to the experimental bones and not persisting across time. In contrast, the haplotype network for O. alborana revealed that none of the haplotypes present in three different trimesters were shared, suggesting that the populations arriving at the bones during each trimester were totally replaced by new individuals during the subsequent trimesters. Our study suggests that different species of shallow‐water Ophryotrocha occurring in the Mediterranean may have different patterns of substrate colonization despite sharing similar life histories.

Life after death: shallow‐water Mediterranean invertebrate communities associated with mammal bones - Sergi Taboada; Maria Bas; Carlos Leiva; Mariona Garriga; Rafael Sardá; Conxita Avila (Marine Ecology, 2016)
Invertebrate and microbial marine communities associated with mammal bones are interesting and poorly understood habitats, mainly known from studies on deep‐water whale remains. In order to characterize these communities in the shallow‐water Mediterranean, we present here the results of a pioneering experiment using mammal bones. Minke whale, pig and cow bones were experimentally deployed on three different background communities: rocky substrate, soft‐bottom and a Posidonia oceanica meadow. Bones were deployed for a year at about 20 m depth and collected every 3 months, and the invertebrate fauna colonizing the bones was identified to the lowest possible taxonomic level. As expected, mammal bones showed remarkable differences when compared with background communities. Within bones, four different clusters could be identified, primarily on the basis of the polychaete fauna, the most abundant and diverse group in the survey. Clusters A1–A3 corresponded to high to moderately altered successional stages composed by a fauna closer to that of anthropogenically enriched shallow‐water environments. These clusters were characterized by the occurrence of the opportunist polychaetes Ophryotrocha puerilis , Neanthes caudata (Cluster A1), Protodorvillea kefersteini (Cluster A2) and Ophryotrocha alborana (Cluster A3). Cluster B was characterized by the presence of the polychaete Oxydromus pallidus together with typical invertebrate background fauna, which suggests that this community, after a year of deployment, was closer to that found in natural conditions. As opposed to similar shallow‐water studies in other geographic areas, no occurrence of the polychaete Osedax (commonly known as bone‐eating worms) was reported from our experiments. Apart from the study on the invertebrate communities, insights about the population dynamics of three of the most abundant species ( O. puerilis , O. alborana , N. caudata ) are given as well as remarks on a hypothetical trophic network based on fecal pellet analysis.

Multi-model comparison of the economic and energy implications for China and India in an international climate regime - Daniel J. A. Johansson; Paul L. Lucas; Matthias Weitzel; Erik O. Ahlgren; A. B Bazaz; Wenying Chen; Michel G. J. den Elzen; Joydeep Ghosh; Maria Grahn; Qiao-Mei Liang; Sonja Peterson; Basanta K. Pradhan; et al. (Mitigation and Adaptation Strategies for Global Change, 2015)

A new Parougia species (Annelida, Dorvilleidae) associated with eutrophic marine habitats in Antarctica - Sergi Taboada; Maria Bas; Conxita Avila (Polar Biology, 2015)

Acquisition and loss of desiccation tolerance in seeds: from experimental model to biological relevance - Bas J. W. Dekkers; Maria Cecilia D. Costa; Julio Maia; Leónie Bentsink; Wilco Ligterink; Henk W. M. Hilhorst (Planta, 2015)

Enhancing the relevance of Shared Socioeconomic Pathways for climate change impacts, adaptation and vulnerability research - Bas J. van Ruijven; Marc A. Levy; Arun Agrawal; Frank Biermann; Joern Birkmann; Timothy R. Carter; Kristie L. Ebi; Matthias Garschagen; Bryan Jones; Roger Jones; Eric Kemp-Benedict; Marcel Kok; et al. (Climatic Change, 2014)

Is the blue tit falling into an ecological trap in Argentine ant invaded forests? - David Estany-Tigerström; Josep Maria Bas; Miguel Clavero; Pere Pons (Biological Invasions, 2013)

Anthropometric characteristics and risk of lymphoid and myeloid leukemia in the European Prospective Investigation into Cancer and Nutrition (EPIC) - Fatemeh Saberi Hosnijeh; Isabelle Romieu; Valentina Gallo; Elio Riboli; Anne Tjønneland; Jytte Halkjær; Guy Fagherazzi; Françoise Clavel-Chapelon; Laure Dossus; Annie Lukanova; Rudolf Kaaks; Antonia Trichopoulou; et al. (Cancer Causes & Control, 2013)

EURRECA—Evidence-Based Methodology for Deriving Micronutrient Recommendations - Rosalie A. M. Dhonukshe-Rutten; Jildau Bouwman; Kerry A. Brown; Adriënne E. J. M. Cavelaars; Rachel Collings; Evangelia Grammatikaki; Lisette CPGM de Groot; Mirjana Gurinovic; Linda J. Harvey; Maria Hermoso; Rachel Hurst; Bas Kremer; et al. (Critical Reviews in Food Science and Nutrition, 2013)

Prediagnostic concentrations of plasma genistein and prostate cancer risk in 1,605 men with prostate cancer and 1,697 matched control participants in EPIC - Ruth C. Travis; Naomi E. Allen; Paul N. Appleby; Alison Price; Rudolf Kaaks; Jenny Chang-Claude; Heiner Boeing; Krasimira Aleksandrova; Anne Tjønneland; Nina Føns Johnsen; Kim Overvad; J. Ramón Quirós; et al. (Cancer Causes & Control, 2012)

Consumption of meat and fish and risk of lung cancer: results from the European Prospective Investigation into Cancer and Nutrition - Jakob Linseisen; Sabine Rohrmann; Bas Bueno-de-Mesquita; Frederike L. Büchner; Hendriek C. Boshuizen; Antonio Agudo; Inger Torhild Gram; Christina C. Dahm; Kim Overvad; Rikke Egeberg; Anne Tjønneland; Heiner Boeing; et al. (Cancer Causes & Control, 2011)

Coping with invasive alien species: the Argentine ant and the insectivorous bird assemblage of Mediterranean oak forests - Pere Pons; Josep Maria Bas; David Estany-Tigerström (Biodiversity and Conservation, 2010)

Does Argentine ant invasion affect prey availability for foliage-gleaning birds? - David Estany-Tigerström; Josep Maria Bas; Pere Pons (Biological Invasions, 2010)

Lifestyle factors and serum androgens among 636 middle aged men from seven countries in the European Prospective Investigation into Cancer and Nutrition (EPIC) - Reiko Suzuki; Naomi E. Allen; Paul N. Appleby; Timothy J. Key; Laure Dossus; Anne Tjønneland; Nina Føns Johnsen; Kim Overvad; Carlotta Sacerdote; Domenico Palli; Vittorio Krogh; Rosario Tumino; et al. (Cancer Causes & Control, 2009)

Lifestyle factors and serum androgens among 636 middle aged men from seven countries in the European Prospective Investigation into Cancer and Nutrition (EPIC) - Reiko Suzuki; Naomi E. Allen; Paul N. Appleby; Timothy J. Key; Laure Dossus; Anne Tjønneland; Nina Føns Johnsen; Kim Overvad; Carlotta Sacerdote; Domenico Palli; Vittorio Krogh; Rosario Tumino; et al. (Cancer Causes & Control, 2009)

Ethanol intake and the risk of pancreatic cancer in the European prospective investigation into cancer and nutrition (EPIC) - Sabine Rohrmann; Jakob Linseisen; Alina Vrieling; Paolo Boffetta; Rachael Z. Stolzenberg-Solomon; Albert B. Lowenfels; Majken K. Jensen; Kim Overvad; Anja Olsen; Anne Tjonneland; Marie-Christine Boutron-Ruault; Francoise Clavel-Chapelon; et al. (Cancer Causes & Control, 2009)

Intake of fruits and vegetables and risk of cancer of the upper aero-digestive tract: the prospective EPIC-study - Heiner Boeing; Thomas Dietrich; Kurt Hoffmann; Tobias Pischon; Pietro Ferrari; Petra H. Lahmann; Marie Christine Boutron-Ruault; Francoise Clavel-Chapelon; Naomi Allen; Tim Key; Guri Skeie; Eiliv Lund; et al. (Cancer Causes & Control, 2006)

Intestinal lipid absorption is not affected in CD36 deficient mice - Jeltje R. Goudriaan; Vivian E.H. Dahlmans; Maria Febbraio; Bas Teusink; Johannes A. Romijn; Louis M. Havekes; Peter J. Voshol (Molecular and Cellular Biochemistry, 2002)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)